(untitled) (Al-Qamar, 2020)
The economic well-being of a state today is a great challenge. Islam claims that the principles and ideologies it has are the guarantors of economic well-being of the modern Islamic state and the protection of the society from the worsening economic conditions. One of these principles is the principle of Infāq (almsgiving) which means to spend the earnings on God’s deserving creatures for the sake of His pleasure. This paper aims to know how many economic problems of the individual and society can be solved if the Islamic principle of almsgiving is followed according to its true spirit! The Study is based on the Qur’ānic verses and Prophetic traditions. It concludes that Islamic concept of almsgiving is the guarantor of economic well-being of the individual and society. When the state and society observe this principle wealth will come into circulation, the poor and backward sections of the society will also be able to have a better standard of living. As a result, poverty and destitution will be eradicated and the individual and society will prosper.